Paleoenvironments reconstructed from the analyses of loess sequences on Susak Island, Adriatic Sea - Kis, Éva; Schweitzer, Ferenc; Lóczy , Dénes (Acta Geographica Debrecina Landscape & Environment series, 2017)
Susak Island is the outermost member of the archipelago of the Kvarner Bay, North Adriatic Sea, Croatia. Its long-term landscape evolution is defined by tectonic movements. Most characteristic are partly exhumed landforms of an ancient terrane (scarps, uplifted limestone cliffs) in a still active neotectonic environment, but the most appropriate tools for the reconstruction of Quaternary paleoenvironments are loess and loess-like deposits. The Quaternary sequence is up to almost 100 m thickness locally and intensively studied by numerous disciplines (from structural geology to geochemistry and geomorphology) today. The special location of the island makes it a key area of research into the evolution of the broader environment, including the Po Plain as well as other Italian source areas of wind-borne and redeposited dust. The loess mantle was also of great importance for a paleoecological reconstruction of floral and faunal evolution, on which efforts of nature conservation are founded.